2020
DOI: 10.3390/agriculture10090394
|View full text |Cite
|
Sign up to set email alerts
|

Legume Cover Crops as One of the Elements of Strategic Weed Management and Soil Quality Improvement. A Review

Abstract: The benefits of conservation practices increased the interest of farmers in the cultivation of cover crops (CCs). This review aims to present and analyze the state of the art on the cultivation of legume CCs, including their importance in protecting crops against weeds, as well as their effects on organic matter and nitrogen content in the soil, physical and biological properties of the soil, and its erosion. The multi-purpose character of legume CCs is visible in their positive effect on reducing weed infesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 241 publications
(387 reference statements)
1
28
0
Order By: Relevance
“…Nowadays, a sustainable approach to farming practices can refer to conservation of agriculture principles such as minimum soil disturbance and permanent soil cover with cover crops and mulches. The adoption of cover crops within the cropping systems can provide several benefits, i.e., reducing the need for fertilizers by recycling nutrients and fixing the atmospheric N in case of legume cover crops, reducing the incidence of soil-borne disease by providing habitat for beneficial insects, decreasing herbicide use by reducing weed pressure and increasing crop yield by improving soil health [5,6]. While it has been largely recognized that conservation tillage increases soil organic matter, soil structure and stability, which in turn reduce soil erosion, improve water holding capacity and microbial and earthworm activity [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, a sustainable approach to farming practices can refer to conservation of agriculture principles such as minimum soil disturbance and permanent soil cover with cover crops and mulches. The adoption of cover crops within the cropping systems can provide several benefits, i.e., reducing the need for fertilizers by recycling nutrients and fixing the atmospheric N in case of legume cover crops, reducing the incidence of soil-borne disease by providing habitat for beneficial insects, decreasing herbicide use by reducing weed pressure and increasing crop yield by improving soil health [5,6]. While it has been largely recognized that conservation tillage increases soil organic matter, soil structure and stability, which in turn reduce soil erosion, improve water holding capacity and microbial and earthworm activity [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was confirmed that the level of damage after herbicide application and the regeneration rate of camelina plants depended on the cultivar [17]. The review article presents the ecosystem advantages of legume cover crops, including their effect on weed control [18].…”
Section: Introductionmentioning
confidence: 87%
“…They reduce weeds and provide other benefits to farming systems, such as improving soil quality [43]. In particular, the wider use of legume CCs is justified in cropping systems with the limited use of mineral fertilizers and pesticides [18].…”
Section: Chemical and Nonchemical Methods Of Plant Protectionmentioning
confidence: 99%
“…The increasing interest of producers and researchers in cover crops may have been encouraged by the many positive aspects attributed to cover cropping such as improving soil fertility and controlling pests, weeds and erosion (Altieri et al, 2011;Kocira et al, 2020;Koohafkan et al, 2012;Snapp et al, 2005). In particular, cover crops provide direct weed control during their establishment by competing with weeds for light, water, nutrients and space (Blanco-Canqui et al, 2015), as well as releasing allelochemical compounds into the environment (Farooq et al, 2011).…”
Section: Cover Crop Performance and Weed Controlmentioning
confidence: 99%
“…Bhaskar et al, 2018;Mennan et al, 2000;Ranaivoson et al, 2018). Cover crops are thus increasingly used in innovative cropping systems to favor biological regulation and to deliver agro-ecosystem services such as improving soil fertility and controlling pests, weeds and erosion (Altieri et al, 2011;Kocira et al, 2020;Koohafkan et al, 2012;Snapp et al, 2005). A wide range of cover crops are available, so the choice of species to deliver these services is crucial because the spatial and temporal combinations with the main crop will determine the performances of the system (Malezieux et al, 2009).…”
Section: Introductionmentioning
confidence: 99%